Patient preferences for adjuvant radiotherapy in early breast cancer are strongly influenced by treatment received through random assignment. (14th January 2019) - Corica, Tammy; Saunders, Christobel M.; Bulsara, Max K.; Taylor, Mandy; Joseph, David J.; Nowak, Anna K.
Abstract: Objective: TARGIT‐A randomised women with early breast cancer to receive external beam radiotherapy (EBRT) or intraoperative radiotherapy (TARGIT‐IORT). This study aimed to identify what extra risk of recurrence patients would accept for perceived benefits and risks of different radiotherapy treatments. Methods: Patient preferences were determined by self‐rated trade‐off questionnaires in two studies: Stage (1) 209 TARGIT‐A participants (TARGIT‐IORT n  =   108, EBRT n  =   101); Stage (2) 123 non‐trial patients yet to receive radiotherapy (pre‐treatment group), with 85 also surveyed post‐radiotherapy. Patients traded‐off risks of local recurrence in preference selection between TARGIT‐IORT and EBRT. Results: TARGIT‐IORT patients were more accepting of IORT than EBRT patients with 60% accepting the highest increased risk presented (4%–6%) compared to 12% of EBRT patients, and 2% not accepting IORT at all compared to 43% of EBRT patients. Pre‐treatment patients were more accepting of IORT than post‐treatment patients with 23% accepting the highest increased risk presented compared to 15% of post‐treatment patients, and 15% not accepting IORT at all compared to 41% of pre‐treatment patients. Conclusions: Breast cancer patients yet to receive radiotherapy accept a higher recurrence risk than the actual risk found in TARGIT‐A. Measured patient preferences are highly influenced by experience of treatment received. This finding challenges the validity of post‐treatment preference studies.